Body image perception is associated with nutritional status of adolescent girls: A cross-sectional study in Denpasar City, Bali Province, Indonesia - I Gusti Ayu Komang Widiastuti; Ni Ketut Sutiari; Luh Seri Ani (Public Health and Preventive Medicine Archive, 2023)
Background and purpose: Adolescent psychopathological conditions influence body image perception which can lead to eating disorders, resulting in nutritional and health problems The objective of this study is to analyze the relationship between body image perception, eating disorders, and the nutritional status of adolescent girls. Methods: This is a quantitative observational study using a cross-sectional design. The study was conducted at SMP Negeri 8 Denpasar and SMP Raj Yamuna in 2022 involving 90 students. Data collected included characteristics, body image perception, eating disorders, weight, and height. Data collection instruments included questionnaire, Multidimensional Body Self Relations Questionnaire-Appearance Scales (MBSRQ-AS) for body image perception, anthropometric measurement tools and the Eating Disorder Diagnostic Scale (EDDS). The data was analysed including descriptive analysis and Chi-square test. Results: The respondents were aged between 12–15 years, with the highest proportion was age 13 years at 42.2%. The majority of adolescent girls (44.8%) were in grade VIII. More than half (54.4%) tend to have a positive body image perception, whilst the majority experienced eating disorders at 86.7%, and had normal nutritional status at 75.6%. Body image perception associated with nutritional status of adolescent girls (OR=4.587; 95%CI: 1.589-13.237; p=0.003). Conclusion: Body image perception is related to the nutritional status of adolescent girls in Denpasar. Therefore, peer counselors are needed to improve adolescent communication, including promoting nutritional action messages through appealing social media approaches. Then, interventions at school are also needed including to define the role of peer supports.